Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/chem.200903210
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Imidazolium‐Based Rodlike Ionic Liquid Crystals: Transition from Lamellar to Micellar Organization

Abstract: By using aryl-amination chemistry, a series of rodlike 1-phenyl-1H-imidazole-based liquid crystals (LCs) and related imidazolium-based ionic liquid crystals (ILCs) has been prepared. The number and length of the C-terminal chains (at the noncharged end of the rodlike core) and the length of the N-terminal chain (on the imidazolium unit in the ILCs) were modified and the influence of these structural parameters on the mode of self-assembly in LC phases was investigated by polarizing microscopy, differential sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 122 publications
7
77
1
5
Order By: Relevance
“…The only other examples of such behaviour for imidazolium ionic liquid crystals have only very recently been reported. [23,29] A transition from lamellar mesophases (with flat interfaces) to columnar mesophases (with curved interfaces), via an intermediate cubic structure, is typically found for tetracatenar liquid crystals. [46][47][48][49][50][51] This is explained by the increase in the aliphatic volume fraction with temperature and/or chain length.…”
Section: Abstract In Dutchmentioning
confidence: 99%
See 2 more Smart Citations
“…The only other examples of such behaviour for imidazolium ionic liquid crystals have only very recently been reported. [23,29] A transition from lamellar mesophases (with flat interfaces) to columnar mesophases (with curved interfaces), via an intermediate cubic structure, is typically found for tetracatenar liquid crystals. [46][47][48][49][50][51] This is explained by the increase in the aliphatic volume fraction with temperature and/or chain length.…”
Section: Abstract In Dutchmentioning
confidence: 99%
“…www.chemeurj.org 6) Finally, Tschierske et al reported four rod-like imidazolium bromide compounds containing three tetradecyl or hexadecyl chains that exhibited micellar Cub Pm3 n phases. [29] The following sections describe the X-ray diffraction data that were obtained for our 2-arylsubstituted imidazolium salts. The crystalline nature of the solid phases at room temperature was confirmed by the presence of several sharp Bragg reflections at both small and wide angles.…”
Section: Abstract In Dutchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the nematic phase is commonly used in electrooptical devices. The nematic phase is quite rare in the case of ILCs, several examples have been reported so far for ammonium [43,44], imidazolium [45][46][47][48], pyridinium-based ILC [49], or miscellaneous type of ILC [50][51][52][53][54]. Generally, as the smectic phases are the most common phases for ILCs, especially due to electrostatic interactions, the nematic phase can be seen rather as an exception.…”
Section: Nematic Pyridinium Ionic Liquid Crystalsmentioning
confidence: 99%
“…[11] Imidazolium-based ILCs including symmetrical and unsymmetrical molecular frameworks have been generated and most of them show smectic phases. [12] Recently, mesomorphic imidazolium salts were also used as new vectors for small interfering RNA (siRNA) transfection. [13] Most of the organic compounds known for optoelectronic applications still have some major limitations such as low electron conductivity or luminescence efficiency.…”
Section: Introductionmentioning
confidence: 99%